Bycatches of harbour porpoises (Phocoena phocoena L.) in Danish set-net fisheries - Winther, Morten (J. Cetacean Res. Manage., 1999)
Data on bycatch of harbour porpoise (Phocoena phocoena L.) in the commercial Danish set-net fisheries were sampled from 5,591km nets in the period 1992 to 1998 using independent observers. A total bycatch of 325 harbour porpoises was reported. Cluster analysis was used to stratify the sampled fishing trips and official catch statistics into a number of different m6tiers defined by the target species for the trips. Extrapolation of the observed bycatch rate to total fish landings of the Danish set-net fleet gave an average annual bycatch of 6,785 (CV 0.12) for the North Sea fisheries in the period 1994-1998. Sampling was not sufficient to estimate total bycatch for other areas. Bycatch was observed in Kattegat but not in the Baltic Sea. Generalised Linear Models were used to identify significant factors for bycatch in the North Sea. The bycatch rate, given as number per length of nets x soak time, was significantly lower in fisheries for flatfish compared to roundfish fisheries. The highest bycatch rate was in the cod fishery over wrecks and no bycatch was observed in the sole fishery. Significant seasonal variation of bycatch was identified with the highest bycatch rate in the first and third quarter of the year. Bycatch rates had not changed in the observed period and there was no significant difference in bycatch rates between sub-areas.